Thermophilic biohydrogen production by an anaerobic heat treated-hot spring culture - Karadag, Dogan; Makinen, Annukka E.; Efimova, Elena; Puhakka, Jaakko A. (ELSEVIER SCI LTD, 2009)
Batch experiments were conducted to investigate the thermophilic biohydrogen production using an enrichment culture from a Turkish hot spring. Following the enrichment, the culture was heat treated at 100 degrees C for 10 min to select for spore-forming bacteria. H-2 production was accompanied by production of acetate, butyrate, lactate and ethanol. H-2 Production was associated by acetate-butyrate type fermentation while accumulation of lactate and ethanol negatively affected the H-2 yield. H-2 production was highest in the temperature range from 49.6 to 54.8 degrees C and optimum values for initial PH and concentral ions of iron, yeast extract and glucose were 6.5, 40 mg/l, 4-13.5 g/l, respectively. PCR-DGGE profiling showed that the heat treated culture consisted of species closely affiliated to genus Thermoonaerobacterium. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Biohydrogen production; Thermophilic; Thermoanaerobacterium; Hot spring; VFA; FERMENTATIVE HYDROGEN-PRODUCTION; MICROBIAL COMMUNITY; WASTE-WATER; FEASIBILITY; MICROFLORA; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels